An Economic Theory of Greed, Love, Groups, and Networks / [electronic resource] - Frijters, Paul (Cambridge : Cambridge University Press, 2013)
Why are people loyal? How do groups form and how do they create incentives for their members to abide by group norms? Until now, economics has only been able to partially answer these questions. In this groundbreaking work, Paul Frijters presents a new unified theory of human behaviour. To do so, he incorporates comprehensive yet tractable definitions of love and power, and the dynamics of groups and networks, into the traditional mainstream economic view. The result is an enhanced view of human societies that nevertheless retains the pursuit of self-interest at its core. This book provides a digestible but comprehensive theory of our socioeconomic system, which condenses its immense complexity into simplified representations. The result both illuminates humanity's history and suggests ways forward for policies today, in areas as diverse as poverty reduction and tax compliance.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Avarice; Economic man; Reciprocity (Commerce); Social groups; Social networks